Micro-learning and Mindtools in Mobile-Learning (M-Learning): effects on knowledge and self-efficacy in laparoscopy education for surgical nursing students - Fatemeh Akbari HajiAbad; Fatemeh Keshmiri; Fatemeh Jabinian; Seyed Mostafa Shiryazdi (BMC Nursing)
Abstract Background In this study, an online Mobile-Learning (M-learning) application was developed based on the principles of mindtools and micro-learning strategy to educate surgical nursing students in laparoscopic surgical units. This study aimed to assess the effect of education using M-learning in laparoscopic surgical units on nursing students’ knowledge and self-efficacy. Method This experimental study was conducted at Shahid Sadoughi University of Medical Sciences from 2022 to 2023. Surgical nursing students were included in the study (n = 57) and were classified into intervention and control groups using random sampling. This educational program aimed to develop learners’ ability to recognize laparoscopic surgical tools and diagnose appropriate tools in laparoscopic surgery steps using scrub and circular techniques. The students in the intervention group used M-Learning during workplace-based learning in the surgical laparoscopy unit. Students’ training in the control group included routine clinical education, including observation and practice. The students in both groups participated in a knowledge examination (n = 13 questions) and self-efficacy assessment before and one week after. The data were summarized using descriptive statistics and analyzed using Pearson’s test and Student t-test. The effect size of the educational intervention on the variables was reported using Partial Eta Square. Results The results revealed significant differences in knowledge scores between the intervention and control groups after the training (P-value = 0.004, partial η² = 0.11). However, the difference in self-efficacy between the two groups after the intervention was not statistically significant (P-value = 0.148, partial η² = 0.03). Conclusion The present study used M-learning with a Mindtools strategy as a complementary tool in clinical education. The findings indicated that the intervention’s educational effect on learners’ knowledge was favorable, while the educational effect on students’ self-efficacy was moderate. In conclusion, this M-learning application tool in clinical training planning is proposed as a support tool to improve students’ capabilities in clinical training programs. Trial registration number (TRN) In our context, clinical studies in the patient community have criteria for receiving a TRN code. Educational interventions in the student community have not been assessed because they are not eligible for the trial code. The study has been reviewed and approved by the ethics committee. We have added a certificate in the supplementary section.